2022
DOI: 10.1016/j.scitotenv.2022.153816
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 RNA in wastewater, river water, and hospital wastewater of Nepal

Abstract: The applicability of wastewater-based epidemiology (WBE) has been extensively studied throughout the world with remarkable findings. This study reports the presence and reduction of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) at two wastewater treatment plants (WWTPs) of Nepal, along with river water, hospital wastewater (HWW), and wastewater from sewer lines collected between July 2020 and February 2021. SARS-CoV-2 RNA was detected in 50%, 54%, 100%, and 100% of water samples from WWTPs, rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…SARS-CoV-2 RNA was detected in two natural surface water sources (Dam reservoir_C and Dam reservoir_P), as had already happened in other countries—namely, Italy [ 11 ], Mexico [ 13 ], Brazil [ 14 ], and Nepal [ 15 ]. However, in the referred studies, the viral RNA was detected in water samples taken from rivers—not from dam reservoirs, as occurred in the present project.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…SARS-CoV-2 RNA was detected in two natural surface water sources (Dam reservoir_C and Dam reservoir_P), as had already happened in other countries—namely, Italy [ 11 ], Mexico [ 13 ], Brazil [ 14 ], and Nepal [ 15 ]. However, in the referred studies, the viral RNA was detected in water samples taken from rivers—not from dam reservoirs, as occurred in the present project.…”
Section: Discussionmentioning
confidence: 84%
“…In Brazil, in a study by Fongaro et al [ 14 ] in August 2020, viral RNA was found in the water of a river downstream of a rural community in Minas Gerais (1.1 × 10 2 gc/mL). In Nepal, Tandukar et al [ 15 ] detected SARS-CoV-2 RNA in the water of a river at a concentration of 4.0 to 5.0 log10 gc/L, in addition to also having been found in wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the numerous reports of the presence of SARS-CoV-2 in wastewater systems during the pandemic, the number of studies reporting its incidence in freshwater or surface water is relatively limited (Table S1). River waters were positive for SARS-CoV-2 RNA in Nepal (4–5 × 10 4 copies/L), the Minas Gerais state of southern Brazil (1.1 × 10 5 copies/L), the Monterrey metropolitan area of Mexico (2.5–7.0 × 10 3 copies/L), the Danube River in Serbia (5.97 × 10 3 –1.32 × 10 4 copies/L), the Indian cities of Ahmedabad and Guwahati (800 copies/L for the Sabarmati River and 565 copies/L for the Bharalu urban river), and the Tijuana River at two locations downstream of the United States–Mexico border in California (10 3.4 –10 7.2 copies/L). River samples collected in Yamanashi Prefecture, Japan, between April 22 and May 7, 2020, were negative .…”
Section: Discussionmentioning
confidence: 99%
“… 18 In a study of three rivers in Italy during April 2020, the presence of SARS-CoV-2 RNA was detected but virus concentrations were not quantified. 4 SARS-CoV-2 RNA in river samples receiving discharge of untreated wastewater during June 2020 in Ecuador, 19 October 2020 through January 2021 in Mexico, 20 July 2020 through February 2021 in Nepal, 21 and December 2020 in Serbia 22 were detected and quantified, but these studies generally relied on discrete or one-time sample collection, have river water samples receiving secondary treated wastewater effluent 23 (as opposed to raw sewage), and did not make inference about trends in concentrations. As such, more needs to be discovered about the temporal trends and relationships with community infectivity for wastewater-impaired surface waters and open channel sewage conveyance systems.…”
Section: Introductionmentioning
confidence: 99%